How to select relevant metabolites based on available data for parent molecules: Case of neonicotinoids, carbamates, phenylpyrazoles and organophosphorus compounds in French water resources. (October 2020) - Melin, Jodie; Guillon, Amélie; Enault, Jérôme; Esperanza, Mar; Dauchy, Xavier; Bouchonnet, Stéphane
Abstract: The presence of pesticide in water resources is a topical issue in France as in many other countries. Resources can be contaminated by current-used pesticides and their metabolites but also by molecules banned 50 years ago. The number of reported studies on the impact of these substances on human health and environment increases every day. Currently, pesticides and their relevant degradation products are subjected to the European regulation for water intended for human consumption. It sets an individual quality limit of 0.1 μg/L, and another of 0.5 μg/L for the sum of their concentrations. The constant improvement of analytical methods allows laboratories to detect pesticides, at lower and lower concentrations but also more and more metabolites. However, regulation does not provide a national indicative metabolites list to be monitored. Each regional health agency offers their own list based on local agricultural practices and quantities of pesticides sold. This article reports a prioritization method allowing to identify new metabolites to be monitored in water resources, along drinking water treatment plants and in treated water; it describes its application in France in order to anticipate possible non-compliance with raw water and treated water and to provide solutions upstream of changes in sanitary control. This methodology has been developed to rank pesticides and to select the corresponding metabolites by combining three main criteria: use (sale and type of use), toxicity, and environmental fate (based on physical and chemical properties). Prioritization method was applied to four families of pesticides: carbamates, organophosphorus compounds, phenylpyrazoles and neonicotinoids, for which there is a real lack of knowledge as regards the occurrence of their metabolites in metropolitan France. 146 pesticides have been prioritized. The first 50 molecules were considered allowing the identification of 72 metabolites to be monitored in water resources and along drinking water treatment plants. Graphical abstract: Image 1 Highlights: A prioritization methodology has been developed for pesticides and their metabolites. Carbamates, organophosphates, phenylpyrazoles and neonicotinoids were selected. 146 molecules were prioritized based on use, toxicity and environmental fate.